Innate neuroimmunity across aging and neurodegeneration: a perspective from amyloidogenic evolvability - Ho, Gilbert; Lam, Linh; Tran, Tony; Wei, Jianshe; Hashimoto, Makoto (Frontiers in Cell and Developmental Biology, 2024)
In Alzheimer's Disease (AD), amyloidogenic proteins (APs), such as β-amyloid (Aβ) and tau, may act as alarmins/damage-associated molecular patterns (DAMPs) to stimulate neuroinflammation and cell death. Indeed, recent evidence suggests that brain-specific type 2 immune networks may be important in modulating amyloidogenicity and brain homeostasis. Central to this, components of innate neuroimmune signaling, particularly type 2 components, assume distinctly specialized roles in regulating immune homeostasis and brain function. Whereas balanced immune surveillance stems from normal type 2 brain immune function, appropriate microglial clearance of aggregated misfolded proteins and neurotrophic and synaptotrophic signaling, aberrant pro-inflammatory activity triggered by alarmins might disrupt this normal immune homeostasis with reduced microglial amyloid clearance, synaptic loss, and ultimately neurodegeneration. Furthermore, since increased inflammation may in turn cause neurodegeneration, it is predicted that AP aggregation and neuroinflammation could synergistically promote even more damage. The reasons for maintaining such adverse biological conditions which have not been weeded out during evolution remain unclear. Here, we discuss these issues from a viewpoint of amyloidogenic evolvability, namely aEVO, a hypothetic view of an adaptation to environmental stress by AP aggregates. Speculatively, the interaction of AP aggregation and neuroinflammation for aEVO in reproduction, which is evolutionally beneficial, might become a co-activating relationship which promotes AD pathogenesis through antagonistic pleiotropy. If validated, simultaneously suppressing both AP aggregation and specific innate neuroinflammation could greatly increase therapeutic efficacy in AD. Overall, combining a better understanding of innate neuroimmunity in aging and disease with the aEVO hypothesis may help uncover novel mechanism of pathogenesis of AD, leading to improved diagnostics and treatments.